(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The Central Asian region is characterized by the multiethnicity of its population, which includes Kyrgyz, Kazakhs, Uzbeks, Tajiks, and Turkmens. These ethnic groups differ from one another not only in terms of the geographical conditions of their settlements but also in a broad range of historical-anthropological, cultural, social, economic, political, and other features. However, despite these differences, an important factor in shaping various types of identity among the peoples and tribes inhabiting a particular region is cultural and historical homogeneity, which significantly contributes to their linguistic, religious, and overall spiritual similarities. On the other hand, historical upheavals and events inevitably influence the current state of affairs and ongoing processes in modern Central Asia. In this regard, Central Asian states face complex challenges in countering new security threats and choosing an adequate and effective system for ensuring regional security. Addressing this issue unambiguously requires the consolidation of efforts, actions, and initiatives from all countries in the region